Innovation in immediate neonatal care: development of the Bedside Assessment, Stabilisation and Initial Cardiorespiratory Support (BASICS) trolley. Issue 2 (10th April 2015) - Weeks, A D; Watt, P; Yoxall, C W; Gallagher, A; Burleigh, A; Bewley, S; Heuchan, A M; Duley, L
Abstract : Objective: Babies receive oxygen through their umbilical cord while in the uterus and for a few minutes after birth. Currently, if the baby is not breathing well at birth, the cord is cut so as to transfer the newborn to a resuscitation unit. We sought to develop a mobile resuscitation trolley on which newly born babies can be resuscitated while still receiving oxygenated blood and the 'placental transfusion' through the umbilical cord. This would also prevent separation of the mother and baby in the first minutes after birth. Design: Multidisciplinary iterative product development. Setting: Clinical Engineering Department of a University Teaching Hospital. Methods: Following an initial design meeting, a series of prototypes were developed. At each stage, the prototype was reviewed by a team of experts in the laboratory and in the hospital delivery suite to determine ease of use and fitness for purpose. A commercial company was identified to collaborate on the trolley's development and secure marking with the Conformité Européenne mark, allowing the trolley to be introduced into clinical practice. Results: The trolley is a small mobile resuscitation unit based on the concept of an overbed hospital table. It can be manoeuvred to within 50 cm of the mother's pelvis so that the umbilical cord can remain intact during resuscitation, irrespective of whether the baby is born naturally, by instrumental delivery or by caesarean section. Warmth for the newborn comes from a heated mattress and the trolley has the facility to provide suction, oxygen and air. Conclusions: This is the first mobile resuscitation device designed specifically to facilitate newborn resuscitation at the bedside and with an intact cord. The next step is to assess its safety, its acceptability to clinicians and parents, and to determine whether it allows resuscitation with an intact cord.